COMPLETELY EDENTULOUS PATIENTS. PART 1: MORPHOLOGICAL FEATURES OF THE UPPER AND LOWER JAW - Nickolay Apostolov; Stefan Zlatev; Elitsa Deliverska; Rangel Todorov (Peytchinski Publishing, 2022)
Aim: The aim of the present research is to characterize the morphological features of the upper and lower jaws in cases of completely edentulous patients. Materials and methods: For the purpose of this study, 96 patients aged 49-88 were examined between 2016-2019. The research was conducted during the practical classes in prosthetic dental medicine and oral and maxilla-facial surgery at the Faculty of Dental Medicine, Medical University - Sofia. The study methods included an individual interview, observation, palpation, and clinical and laboratory measurements. The results were collected in pre-made patient cards. The investigated variables were age, gender, stage of atrophy, the morphological features of the alveolar ridge, and the total period of edentulism and denture usage. Results:The results of the research showed that the second degree of atrophy is the most prevalent condition for both jaws. The third degree of atrophy was associated with the lower jaw but rarely occurred in the upper. The vestibular inclination was typical for the maxillary, frontal alveolar ridge, whereas, in the distal areas, the edentulous ridge was predominantly vertical. The vertical slope of the ridge was prevalent in the three examined areas on the lower jaw. Unequal and asymmetric alveolar ridges were more frequent in the mandible. An association between the time being edentulous and the degree of atrophy was observed in both jaws.